A new species of Nitokra Boeck, 1865 (Copepoda: Harpacticoida: Ameiridae) from a hyporheic zone in central Vietnam - Tran, Ngoc-Son; Trinh-Dang, Mau; Nguyen, Thi Tuong Vi; Brancelj, Anton (Zootaxa, 2025)
A new species of harpacticoid copepod, Nitokra quangnamensis sp. nov. was collected from a hyporheic zone of a river in the central part of Vietnam. It is the second member of the genus described from Vietnam. It belongs to the group III (Gómez et al. 2012), where members have a seta on inner margin of P1 Exp-2 and five setae/spines on P1 Exp-3. The group is also characterized by the number of elements (spines/setae) as: P2–P4 Enp-3 with 4,5,5 elements, P2–P4 Exp-3 with 7,7,7 elements and P2–P4 Enp-1 with 1,1,1 seta on inner margin. The most closely-related species, N. laingensis Fiers, 1986, differs from the new species in: i) N. quangnamensis sp. nov. has seven setae in female P5 Exp, but five setae in N. laingensis; ii) distal segment of a mandibular palp in the new species with six elements, vs. five in N. laingensis; iii) male anal operculum of the new species with six spines, vs. four in N. laingensis.